(untitled) - Leiboff, Marett (Pyrmont, N.S.W., 2009)
Makes legal theory real, by providing readers with examples of the uses of legal theory in practice, an explanation of its methods, and an overview of aspects of the content of legal theory. Looks at how legal theory is used to explain judgements, or analyse the law, enabling students to understand how legal theories are put to use.
Keywords: Triết lý & lý thuyết về pháp luật (Úc),Philosophy &​ theory of law (Australia)